Narrative Study: Diary of Digital Immigrant EFL Teacher In Myanmar - Yam Saroh; Khin Wint War Htun (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2020)
ABSTRACTTeachers, mainly digital immigrants, find challenges to chase technology to integrate digital learning in the classroom. The previous studies revealed that some digital immigrant teachers, the newcomers of the digital age, lacked the confidence to integrate technology during teaching since they were aware of the fact that their students were more proficient than they were. This study depicts the struggles of a digital immigrant EFL teacher-educator to engage with technology that aims at improving the English teaching performance. A digital immigrant EFL teacher from a high-quality education college in Myanmar was invited to be the research participant. Open-ended questionnaires and semi-structured interviews with both the research participant and students were applied to collect the data. The triangulation data revealed that the digital immigrant EFL teacher found difficulties in creating her digital learning media and improving her teaching technology integration competence due to her insufficient knowledge and IT skills. It also revealed that integrating technology improved the teacher's teaching performance; however, it destructed the objectives of the teaching due to technology deviation on students' attention.ABSTRAKGuru, terutama yang imigran digital, mengalami tantangan besar dalam mengejar ketertinggalan mereka terhadap teknologi yang bertujuan mengintegrasikan pembelajaran digital di kelas. Studi sebelumnya mengungkapkan bahwa beberapa guru imigran digital, pendatang baru di era digital, kurang percaya diri untuk mengintegrasikan teknologi selama mengajar karena mereka menyadari fakta bahwa siswanya lebih mahir. Penelitian ini menggambarkan seorang guru-pendidik EFL imigran digital untuk terlibat dengan teknologi yang bertujuan untuk meningkatkan kinerja pengajaran bahasa Inggris. Seorang guru EFL imigran digital dari perguruan tinggi pendidikan berkualitas di Myanmar diundang untuk menjadi peserta penelitian. Kuesioner terbuka dan wawancara semi terstruktur untuk peserta penelitian dan mahasiswa digunakan untuk mengumpulkan data. Triangulasi data mengungkapkan bahwa guru EFL imigran digital mengalami kesulitan dalam media pembelajaran digital dan meningkatkan kompetensi integrasi teknologi karena pengetahuan dan keterampilannya yang kurang di bidang teknologi informasi. Ia juga mengungkapkan bahwa mengintegrasikan teknologi meningkatkan kinerja mengajar guru. Namun, hal itu merusak tujuan pembelajaran karena adanya penyimpangan teknologi yang menjadi perhatian siswa.